Organic Food Labeling and Consumer Perception: Empirical Evidence - Ruiz, Felipe; Muñetón Santa, Guberney; Valencia Cárdenas, Marisol; Restrepo Morales, Jorge Anibal (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sum, 2024)
An impact analysis of consumer perceptions of organic food is proposed, using a quasi-experimental design in a Colombian region, where participants tasted four foods, with two types of labels: organic and conventional. A structural equation model was used to analyze the data, showing that organic labeling promotes healthier food perceptions, but not with better taste, verifying the halo effect by labeling organic products that are in fact conventional, for the following foods: brownie, oatmeal, natural yogurt and cookies, finding that even though all products were conventional, consumers assigned higher ratings to those with organic labels; especially for oatmeal, and crackers, also, brownie but not natural yogurt.